Effects of work-family conflict on turnover intention among primary medical staff in Huaihai Economic Zone: a mediation model through burnout - Wen, Zongliang; Xu, Jintao; Yu, Jinxun; Huang, Xiaojing; Ni, Yuting (Frontiers in Psychiatry, 2023)
Background Countries worldwide face the challenge of how medical personnel manage conflicts between work and family. Especially after the challenge of the COVID-19 epidemic, it is necessary to explore the possible mechanisms of work-family conflict, burnout, and turnover intention among primary medical staff. Objectives This study aims to observe the turnover intention of Chinese primary medical staff and explore the relationship between work-family conflict, burnout, and turnover intention. Methods A cross-sectional study included a turnover intention questionnaire, the Maslach Burnout Inventory-General Survey (MBI-GS), and the Work-Family Conflict Scale (WFCS) to understand turnover intention, burnout, and work-family conflict among primary medical staff in four cities (Xuzhou, Linyi, Huaibei, and Shangqiu cities) within the Huaihai Economic Zone. Spearman correlation analysis and hierarchical multiple regression analysis were used to examine the related factors of turnover intention. Structural equation modeling (SEM) was used to study the mediating role of burnout between work-family conflict and turnover intention. Results In this study, there is a positive correlation between work-family conflict and turnover intention (P < 0.01). Demographic characteristics, work-family conflict, and burnout explained 2.3%, 20.3%, and 8.8% of the incremental variances, respectively. Burnout mediated the association between work-family conflict and turnover intention. Conclusions Burnout can be regarded as a mediator between two different variables: work-family conflict and turnover intention. Improving work-family conflict and alleviating burnout may play a key role in reducing the willingness of primary medical staff to resign. Corresponding measures can be taken to balance the conflict between work and family, alleviate burnout, reduce turnover rates, and build a primary medical staff team with higher medical service quality and stability.